Disrupted Topological Organization of Resting-State Functional Brain Networks in Age-Related Hearing Loss - Yong, Wei; Song, Jiajie; Xing, Chunhua; Xu, Jin-Jing; Xue, Yuan; Yin, Xindao; Wu, Yuanqing; Chen, Yu-Chen (Frontiers in Aging Neuroscience, 2022)
Purpose: Age-related hearing loss (ARHL), associated with function of speech perception decreases characterized by bilateral sensorineural hearing loss at high frequencies, has become an increasingly critical public health problem. To investigate the topological features of brain functional network and structural dysfunction of central nervous system in ARHL using graph theory. Methods: Forty-six patients with ARHL and forty-five age, sex and education-matched healthy controls were recruited to undergo a resting-state functional magnetic resonance imaging (fMRI) scan in this study. Graph theory was applied to analyze topological properties of the functional connectomes by studying the local and global organization of neural networks. Results: Compared to healthy controls, the patient group showed increased local efficiency (Eloc) and clustering coefficient (Cp) of small-world network. Besides, the degree centrality (Dc) and Nodal Efficiency (Ne) values of the left inferior occipital gyrus (IOG) in the patient group showed decreased by contrast with the health control group. In addition, the intra-modular interaction of occipital lobe module and the inter-modular interaction of parietal occipital module decreased in the patient group, which was positively correlated with Dc and Ne. The intra-modular interaction of occipital lobe module decreased in the patient group was negatively correlated with the Eloc. Conclusion: Based on fMRI and graph theory, we indicate the aberrant small-world network topology in ARHL and dysfunctional interaction of occipital lobe and parietal lobe, emphasizing the importance of dysfunctional left IOG. These results suggest that early diagnosis and treatment of patients with ARHL is necessary, which can avoid the transformation of brain topology and decreased brain function.